Analisis Feminis terhadap Variasi Pandangan Emansipasi Perempuan oleh Tokoh March Bersaudara dalam Little Women (2019) - Salsabila, Karina; Hadi, Muhammad Zaki Pahrul (Jurnal Ilmu Sosial dan Humaniora, 2025)
The 2019 film Little Women, a recent adaptation of Louisa May Alcott’s classic novel, presents a compelling narrative centered on women, life choices, and the struggle against social constraints. Directed by Greta Gerwig, the film not only portrays a warm family story but also explores gender dynamics that resonate with contemporary feminist discourse. Through the experiences of the four March sisters Meg, Jo, Beth, and Amy the film becomes a reflection of the diverse and complex forms of female emancipation. This study analyzes Little Women through a feminist lens, employing feminist theory to examine how the film represents gender equality, individual freedom, and resistance to traditional roles within a 19th-century patriarchal society. Each character responds differently to social expectations. Jo, who rejects domestic roles and pursues a writing career, exemplifies liberal feminism and personal agency. Meg consciously embraces marriage and domestic life, illustrating that traditional choices can also be valid forms of empowerment. Amy seeks recognition as an artist while negotiating love and stability, highlighting the multifaceted nature of female identity. Beth, portrayed as gentle and selfless, symbolizes emotional solidarity and sisterhood. The film underscores the significance of women’s autonomy in shaping their own paths and the power of female support systems. By framing the experiences of its characters within both historical and contemporary feminist discourse, Little Women (2019) emerges as a profound and inspiring feminist narrative, one that remains highly relevant in the ongoing pursuit of gender equality and women’s empowerment